A systematic literature review on the impact of CSR awareness on employees’ green behavior in the hospitality industry - Ta, Hoang Giang (Journal of Finance - Marketing Research, 2025)
This study examines the relationship between corporate social responsibility (CSR) awareness and employee green behavior (EGB) in the hospitality industry. Although corporate social responsibility is widely regarded as a driver of sustainability, its specific influence on employees’ green actions remains underexplored, especially in developing contexts such as Vietnam. Using the PRISMA systematic review method, 34 peer-reviewed studies were analyzed to synthesize existing evidence and propose an integrated conceptual model. Findings indicate that corporate social responsibility awareness affects employee green behavior both directly and indirectly through organizational trust (OT) and organizational reputation (OR). The review also emphasizes the distinction between compulsory and voluntary green behaviors, which clarifies employees’ intrinsic motivations. The study contributes theoretically by linking corporate social responsibility awareness, organizational trust, and OR to employee green behavior in a unified framework, and practically by guiding hospitality firms in Vietnam to design corporate social responsibility strategies that foster sustainable employee behavior.